Antjie Krog: Poetry Is The Answer! - Douman, Bronwyn (WritingThreeSixty: Journal or Research and Creative Text, 2018)
WritingThreeSixty sat down with esteemed author and academic, Professor Antjie Krog, on Thursday 4June 2015, in her office at the University of the Western Cape.